Road and off-road vehicle system dynamics handbook - Mastinu, G. (Giampiero); Plöchl, M. (Manfred) (CRC Press, 2013)
Featuring contributions from leading experts, the Road and Off-Road Vehicle System Dynamics Handbook provides comprehensive, authoritative coverage of all the major issues involved in road vehicle dynamic behavior. While the focus is on automobiles, this book also highlights motorcycles, heavy commercial vehicles, and off-road vehicles. The authors of the individual chapters, both from automotive industry and universities, address basic issues, but also include references to significant papers for further reading. Thus the handbook is devoted both to the beginner, wishing to ac.